Metal-Based Drugs for Treatment of Malaria - Marcelino, Paulo Ricardo Franco (Biomedical Applications of Metals, 2017)
Despite the incessant efforts to decrease exorbitant number of daily deaths, malaria remains a major threat to the public health in many countries. Transmitted by Anopheles mosquitoes, it is caused by infection with Plasmodium parasites that have become resistant to many antimalarial drugs. In this context, series of metal-based compounds have been screened for optimal activity against different Plasmodium species and strains. This chapter briefly reviews current and potential uses of metal complexes (such as iron, cobalt, nickel, gallium, copper, gold, and silver), metal chelators, and organometallic compounds, as interesting medicinal agents that greatly benefits the fight against malaria.